Evaluating the Performance of Mobile Air Compressor Component of Radiator Unit using the Application of Reliability - Orukwowu Umejuru; C. P Ukpaka (International Journal of Pollution: Prevention & Control, 2023)
The application of reliability to monitor and predict the performance of mobile air compressor component of radiator unit was considered in this research. This study demonstrated some of the root causes of the radiator unit failure as effect of temperature and the nature of coolers used, because these two parameters cause corrosion, affect shortage on fluid level and in turn influence the internal heat generated by radiator unit of the mobile air compressor. Adequate measures are projected by the maintenance team to ensure that these two factors identified do not cause shutdown of the gas plant. During the period of investigation, it was revealed that the downtime values were increasing with decrease in the mean time between failures. The study further demonstrates that the reliability of the radiator unit component of the mobile air compressor decreases with time as the cost of unreliability increases. This menace can be controlled on the condition of regular check on each radiator fluid level and internal temperature circulation to avoid heating, which may reduce the thermal properties of tube and shell components of the radiator unit in the mobile air compressor.
Keywords: Evaluating; Performance; application reliability; component; mobile air compressor; radiator unit